2012
DOI: 10.2527/jas.2011-4283
|View full text |Cite
|
Sign up to set email alerts
|

Lactation curve and effects of milking regimen on milk yield and quality, and udder health in Martina Franca jennies (Equus asinus)12

Abstract: Three experiments were conducted on Martina Franca jennies. Experiment 1 tested Wood's model for evaluating the lactation curve. Data from the entire lactation period of 12 jennies were used. The results showed that Wood's model was able to recognize the shape of the lactation curve from pooled data (r(2) = 0.11; P < 0.01), with the lactation peak occurring at 48 d. Individual curves showed wide variability. Experiment 2 aimed to evaluate the effects of the daily number of milkings (1, 3, or 6) and the interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 52 publications
4
30
0
Order By: Relevance
“…Additionally, in this case, it must be specified that this milk is the milk produced after the removal of the foal from the mother. The observed differences can be attributed to the breed as well as to the breeding techniques, such as the number of milkings and the milking interval [21]. The milk produced by Ragusano donkeys confirmed the high level of lactose (on average 6.4 g/100 g) and the low protein content (on average 1.6 g/100 g) reported in all the studies on ass milk, which was carried out in different breeds and continents [22].…”
Section: Discussionsupporting
confidence: 55%
“…Additionally, in this case, it must be specified that this milk is the milk produced after the removal of the foal from the mother. The observed differences can be attributed to the breed as well as to the breeding techniques, such as the number of milkings and the milking interval [21]. The milk produced by Ragusano donkeys confirmed the high level of lactose (on average 6.4 g/100 g) and the low protein content (on average 1.6 g/100 g) reported in all the studies on ass milk, which was carried out in different breeds and continents [22].…”
Section: Discussionsupporting
confidence: 55%
“…However, a superimposed effect of photoperiod and climate on the investigated variables can not be excluded. Nevertheless, the observed decrease of milk Cu and Se and the decrease in milk yield reported for donkeys during lactation (D'Alessandro and Martemucci, 2012;Salimei and Fantuz, 2012) suggest that Cu and Se dietary requirements for lactating donkeys decreases as lactation progresses.…”
Section: Discussionmentioning
confidence: 89%
“…In terms of the quantitative milk production, previous studies on a few mainly European and Chinese donkey breeds, have highlighted a high variability (D'alessandro and Martemucci 2012;Martini et al 2014a;Muhatai et al 2017). Several of these authors have also found that a higher milk yield occurs in the first 3 months of lactation.…”
Section: Discussionmentioning
confidence: 99%